ANALISIS KEMAMPUAN BERPIKIR INTUITIF SISWA SMP DALAM PENYELESAIAN MASALAH PADA MATERI SEGI EMPAT - Rahmad Sugianto; M. Ruskhan Fauza; Siti Inganah (Universitas Islam Nusantara, 2023)
Intuitive thinking is very important to use in solving rectangular area problems. because by thinking intuitively students are able to generate creative inspiration impulsively. The emergence of intuitive thinking in solving rectangular area problems is the solution to getting the right answer. The purpose of this study was to find out students' intuition in solving rectangular area problems. This research is descriptive research with a qualitative approach involving 7 students as potential subjects. Two students become the main subject because the answers meet the indicators of intuitive thinking. procedures in this study: 1) determine the material; 2) make test questions; 3) giving tests to prospective subjects; 4) Analyze the answers of prospective subjects with the indicator rubric; 5) Selected as a subject; 6) Conducting interviews on the subject; 7) Analyze the results of interviews from the subject. Collecting data on students' intuitive thinking in solving rectangular area problems using written test instruments and interview tests. Data analysis in this study consists of three categories of intuitive thinking (Catalic Inference, Power of Synthesis, Common Sense). The results of this study are subjects with catalic inference intuitive thinking categories giving short answers and no logical reasons and subjects with Power of Synthesis intuitive thinking categories giving answers that are less organized while common sense intuitive thinking categories giving thorough answers using complete arguments. The categorization in this study is viewed from indicators of intuitive thinking that have been achieved by students in the process of solving questions and interview tests.